Empowerment Strategy of Dry-land Farmers: Insights from Indonesia - Akhmad Daerobi; Eko Suyono (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2021)
The purpose of this study is to identify the level of empowerment of dry-land farmers and develop a model of strategy for empowering them. This study was done in Â Wonogiri Regency, Central Java Province, Indonesia. The level of empowerment is approached descriptively, while the development of an empowerment strategy uses the Analysis Hierarchy Process (AHP) method. The results shows the level of empowerment of dry-land farmers in those area is still low indicated by the power of access to economic (credit, market information, and technology) and non-economic (lobbying and stakeholders) where each value is less than 50% based on the results of the Focus Group Discussion (FGD) and in-depth interviews with keypersons. Â The empowerment strategy can be carried out by developing production, capital procurement, production technology assistance, and improvement of dry land agroecosystems.